Targeting Breast and Gynecologic Cancers: The Role of Natural Products with Emphasis on Cinnamon and Its Derivatives—Advances in Nanoscale Therapeutics and Adjuvant Strategies - Mary A. Biggs; Ipsita A. Banerjee (Macromol)
Members of the Cinnamomum genus have been utilized for medicinal treatment for millennia. In recent years, particular attention has been given to the bioactive metabolites involved in the medicinal properties of natural products and their extracts. Cinnamon is particularly interesting due to the presence of both terpenoid and polyphenol moieties, both of which have been extensively studied for their medicinal applications in the treatment of a wide range of conditions, from bacterial infection, obesity and diabetes to cancer and cardiovascular pathologies. Here, we reviewed some of the properties of cinnamon and its derivatives cinnamic acid, trans-cinnamaldehyde and beta-caryophyllene. In addition, recent advancements in the application of cinnamon and its derivatives in cancer, particularly focusing on gynecological and breast cancers, which present unique challenges to treatment due to late diagnosis, have been discussed. Current advancements to further enhance the delivery of cinnamon and its derivatives through nanoencapsulation and nanoparticulate strategies as well as the development of novel conjugates and hybrids are also discussed. Additionally, the use of cinnamon and its derivatives as adjuvants with chemotherapeutics that can work synergistically was also touched upon. Overall, biotechnological innovations have enhanced the delivery of natural products such as cinnamon and its derivatives and may pave the path for novel therapeutic strategies with fewer side effects and higher potency. Cinnamon represents a valuable source of developing novel anticancer materials that warrant additional research for development as potential interventions or combination treatments.